Battle grounds : the Canadian military and aboriginal lands - Lackenbauer, P. Whitney (Studies in Canadian military history., 2007)
"Base closures, use of airspace for weapons testing and low-level flying, environmental awareness, and Aboriginal land claims have focused attention in recent years on the use of Native lands for military training. But is the military's interest in Aboriginal lands new? Battle Grounds analyzes a century of government-Aboriginal interaction and negotiation to explore how the Canadian military came to use Aboriginal lands for training. It examines what the process reveals about the larger and evolving relationship between governments and Native communities, and how increasing Aboriginal assertiveness and activism have affected the issue."--Jacket